“Belonging/not-belonging” Franz Kafka: An example to remember - Ribeiro-de-Sousa, Celeste (Estudos Avançados, 2021)
This paper begins with concepts of “belonging/not-belonging” and presents the case of Franz Kafka to illustrate the decisive psychic, social and historical circumstances that led him to poeticize his private feelings of “belonging/not-belonging” in his writings. Finally, it analyzes the very small narrative “Gemeinschaft” (“Community”), which we have translated into Portuguese.